Exploring Academic Staff Perception of Organizational Climate and Organizational Citizenship Behaviour: Lessons from Private Universities In Nigeria - Okeke, Margaret N.; Okoli, Ifeanyi Emmanuel Nuel; Nuel-Okoli, Chinenye Maureen (International Journal of Business, Management and Economics, 2022)
This study explored academic staff perception of organisational climate and organizational citizenship behaviour private universities in Southeast, Nigeria. Five specific objectives, research questions and hypotheses were formulated with the decomposed variables of the study. The study was anchored on Social Exchange Theory (SET). A survey design was carried out using the sampled academic staff in the selected private universities. The study population was 4654 while the sample size was 355 arrived. Data were collected using self-administered questionnaire from the random sample of academic staff of the selected private universities in Southeast Nigeria. The data using descriptive statistics and inferential statistics were used in this study. The results revealed that there is a positive significant relationship between organizational climate and organizational citizenship behaviour. The results showed that there is a significant relationship between the organizational climate dimensions and organizational citizenship behaviour dimensions. This implied that the success of an institution is dependent upon the effective management of organisational climate, which is an important path to the success of employee’s citizenship behaviour. The study recommended that equity and fairness should be entrenched during appointments and promotions so as to reduce incidence of service sabotage among academic staff of private universities. In the spirit of harmony, management of private universities should score collaborative works more than individual outputs in order to encourage teamwork among academic staff